Insilico Analysis of Myostatin Gene in Selected Poultry Species (2018)
Myostatin gene (GDF8) is a member of transforming growth-  superfamily and has been reported to act as a negative regular of skeletal muscle during myogenesis, regulation of adipocyte function in livestock species. This study was carried out to computationally investigate molecular genetic variation and categorize precise mutation in myostation gene in selected poultry species at the studied locus. A total of twenty (20) myostatin nucleotide sequences consisting of chicken (12), quail (4) and turkey (4) were retrieved from the GenBank. Functional analysis of nsSNP using PROVEAN showed three amino acid substitutions (P20Q, Y11F and G3R) in chicken, one in quail (Y100R) and three in turkey (N65P, F155W and K95A) were all returned neutral, suggesting their beneficial impacts. The information from nucleotides sequences showed the interclustering and close relatedness of members of phasianidae family (chicken, quail and turkey).